Tailoring Semiconductor Lateral Multijunctions for Giant Photoconductivity Enhancement - Tsai, Yutsung (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.